(untitled) (Open Herald: Periodical of Methodical Research, 2025)
Cystic echinococcosis (CE) is a zoonotic infection caused by Echinococcus granulosus larval stage, with surgical intervention being the primary treatment, often accompanied by chemotherapy. Nevertheless, existing therapies such as benzimidazole carbamates and scolicidal agents may not always yield desired results. Recently, bovine lacteal fluid was tested on CE-causing Echinococcus granulosus protoscoleces in a laboratory. Protoscoleces were treated with cow’s milk at doses of 4, 8, 12, 16, and 20 μM in vitro. The viability and structural alterations of a substance were evaluated using scanning electron microscopy(SEM) and transmission electron microscopy(TEM), and caspase-3 activity was measured using a colorimetric assay. The investigation revealed significant protoscolicidal effects when added to cow’s milk at doses of 16 μM and 20 μM. After incubing them for 6 days, protoscoleces mortality rates reached 83.24% at 16 μM and 100% at 20 μM. According to SEM study, damage caused by drugs mostly came from the tegument. With more lipid droplets and vacuoles seen after 16 μM cow’s milk exposure, TEM revealed serious interior tissue injury. After 24 hours of cow’s milk incubation, protoscoleces had considerably higher caspase-3 activity than untreated samples. The current investigation displays the significant in vitro scolicidal impact of cow’s milk against E. granulosus protoscoleces. However, further research is required to evaluate its effectiveness in vivo, clarify the precise mechanism of action, and determine any potential side effects